Форми та переваги інклюзивних моделей розвитку агробізнесу - Степаненко, С. В. (My University, 2023)
Стаття присвячена дослідженню науково-прикладних засад побудови моделей інклюзивного розвитку аграрного сектору і сільських територій України. Визначено, що за сучасних умов підвищення рівня інклюзивності агробізнесу доцільно розглядати як ключовий стратегічний напрям досягнення цілей сталого розвитку національної економіки. З огляду на специфіку та тенденції розвитку агросектору економіки України, вітчизняне сільське господарство можна визначити одним з найбільш стабільних видів економічної діяльності, що спроможний у майбутньому забезпечити передумови відродження національної економіки. Для досягнення цієї мети необхідним є пошук шляхів і інструментарію імплементації у практику агрогосподарювання інклюзивних засад і моделей розвитку. У статті визначено сукупність переваг, які спроможна забезпечити для всіх учасників агропродовольчого ланцюга вартості імплементація засад інклюзивності у практичну діяльність агробізнесструктур. Поряд з цим, окреслено також основні виклики та перешкоди, що стримують розвиток інклюзивних процесів у сільському господарстві. На основі опрацювання зарубіжного досвіду було виділено основні форми практичної імплементації моделей інклюзивного аграрного бізнесу. У процесі дослідження було виявлено, що економічним базисом підвищення рівня інклюзивності розвитку сільського господарства і сільських територій постає фінансова аграрна інклюзія. Для характеристики її змісту та характеру у методично-практичній площині було запропоновано відокремити чотири основні її виміри. The article is devoted to researching the scientific and applied foundations of building models of inclusive development of the agricultural sector and rural areas of Ukraine. Under modern conditions, the authors consider it expedient to consider increasing the level of inclusivity of agribusiness as a key strategic direction for achieving the goals of sustainable development of the national economy. Given the specifics and development trends of the agricultural sector of the Ukrainian economy, domestic agriculture can be defined as one of the most stable types of economic activity. In the future, agriculture may be able to provide the prerequisites for the revival of the national economy. In order to achieve this goal, it is necessary to find ways and tools for the implementation of inclusive development principles and models into agricultural practice. The set of advantages that the implementation of the principles of inclusivity in the practical activities of agribusiness structures can provide for all participants of the agri-food value chain is defined in this article. The main challenges and obstacles hindering the development of inclusive processes in agriculture are also identified here. Based on the study of foreign experience, the main forms of practical implementation of models of inclusive agrarian business were selected. Among them: models of contract farming; inclusive models of social farming; microfranchising; agricultural cooperatives, organizations and their group forms; public-private partnership; agricultural land lease agreements and agricultural management. Financial agrarian inclusion was defined as the economic basis for increasing the level of inclusiveness in the development of agriculture and rural areas. To characterize its content and nature in the methodological and practical plane, it was proposed to separate its four main dimensions, among them: 1) kinship, availability of financial resources and digital infrastructure; 2) increasing the efficiency of the use of financial resources; 3) inclusive regulatory agrarian and financial policy; 4) development of the potential of inclusive socially responsible agricultural investment.
Forms and advantages of inclusive models of agribusiness development
Keywords: фінансова інклюзія; інклюзивний агробізнес; inclusive agribusiness; agriculture; rural areas; financial inclusion; population welfare; добробут населення; сталий розвиток; сільське господарство; сільські території